Effect of Fe doping on phase transition of TiO2 nanoparticles synthesized by MOCVD - Othman, Siti Hajar; Abdul Rashid, Suraya; Mohd Ghazi, Tinia Idaty; Abdullah, Norhafizah (Asian Network for Scientific Information, 2010)
Titanium dioxide (TiO2) nanoparticles were prepared via Metal Organic Chemical Vapour Deposition (MOCVD) technique at 400 and 700°C. Different amount of iron (Fe) dopant was introduced inside the MOCVD reactor along with the precursor to produce different Fe dopant concentrations of TiO2 nanoparticles. Transmission Electron Microscope (TEM) results disclosed that increasing the deposition temperature resulted in a significant decrease of the size of TiO2 nanoparticle samples and a narrower size distribution. X-ray diffraction (XRD) results revealed that TiO2 nanoparticle sample deposited at 400°C was amorphous while the sample deposited at 700°C was in anatase crystal structure. Fe doping induced phase transition from amorphous to anatase for sample deposited at 400°C and from anatase to rutile for sample deposited at 700°C. Increased concentration of Fe dopant promoted both phase transitions. Meanwhile, TEM and XRD data disclosed that increased concentration of Fe dopant lead to a decrease in size of the nanoparticles produced.